Stock Market and Economic Development: a Causality Test (Journal of Nepalese Business Studies, 2007)
ABSTRACTAn attempt has been made in this paper to examine the existence of causality relationship between stock market and economic growth based on the time series data for the year 1988 to 2005 using Granger causality test. The study finds the empirical evidence of long-run integration and causality of macroeconomic variables and stock market indicators even in a small capital market of Nepal. The causality has been observed only in real terms but not in nominal variables. In econometric sense, it depicts that the stock market plays significant role in determining economic growth and vice versa. Interestingly, the causation is evident with a lag of 3 to 4 years. Also, the paper reveals the importance of stock market development for fostering economic development. Journal of Nepalese Business Studies 2006/III/1 pp. 36-44